Public Service Bureaucratic Reform at the Office of the Class 1 Immigration Checkpoint for the City of Surabaya - Jonathan Marcopolo; Amirul Mustofa; Ulul Albab; Widyawati Widyawati (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
This study aims to describe and analyze: Public Service Bureaucratic Reform and the factors that support and hinder Public Service Bureaucratic Reform at the Office of the Special Class 1 Immigration Checkpoint for the City of Surabaya. The research method to be used is qualitative descriptive. Data Collection Techniques include: Interviews, Observations, Documentation. The research informant is the Head of the Suarabaya Special Class I Immigration Office. The data analysis technique using interactive model analysis was developed by Miles et al., (2014), namely data condensation, data presentation, and conclusion drawn. The results of the study show that in the institutional aspect in accordance with Law Number 6 of 2011 concerning immigration, the institutional arrangement at the Immigration Office is divided into several parts according to their duties and functions. The current posture of organization is relatively slimmer and flat (not very hierarchical). In the resource aspect, human resource improvement is also carried out through the internal office, namely through performance evaluation meetings. In terms of governance, organizational units/work units within the Surabaya Special Class I Immigration Office currently have and implement systems, procedures, and work mechanisms, as well as service standards that are more standard, clear, efficient, and effective, supported by the optimal use of adequate information and communication technology. Supporting Factors for Bureaucratic Reform at the Special Class I Immigration Office in Surabaya are Productive Apparatus, Representative Policies, and Employee Capacity Building. The inhibiting factor is that there is still a practice of brokerage.